Mavericks of war : the unconventional, unorthodox innovators and thinkers, scholars, and outsiders who mastered the art of war /: the unconventional, unorthodox innovators and thinkers, scholars, and outsiders who mastered the art of war. ([2018]) - Ridler, Jason S
No abstract available